Longer-term virologic outcomes on tenofovir-lamivudine-dolutegravir in second-line ART - Jennifer K. van Heerden; Ying Zhao; Claire M. Keene; Rulan Griesel; Zaayid Omar; René Goliath; Kayla Delaney; Gert van Zyl; Gary Maartens; Graeme Meintjes (Southern African Journal of HIV Medicine)
Background: Dolutegravir in second-line antiretroviral therapy (ART) is more effective with recycled tenofovir than switching to zidovudine. However, dolutegravir resistance is more frequent in second-line compared to first-line ART.